Biofertilization with Gluconacetobacter diazotrophicus and Funneliformis mosseae in Guinea grass (Megathyrsus maximus cv. Likoni). Technical note - González, P. J.; Ramírez, J. F.; Reyes, R.; Rivera, R. (Cuban Journal of Agricultural Science, 2022)
An experiment was carried out under semi-controlled conditions to evaluate the effect of biofertilization with Gluconacetobacter diazotrophicus and Funneliformis mosseae on Guinea grass (Megathyrsus maximus cv. Likoni). Five treatments (simple and combined inoculation with G. diazotrophicus and F. mosseae, fertilization with 25 mg N kg-1 of soil and a control without biofertilizers or nitrogenous fertilizer) were studied in a completely random design with five repetitions. Biofertilization with G. diazotrophicus and F. mosseae separately produced higher effects than the control without biofertilizers. However, with the combined application of both, the highest frequency of mycorrhizal colonization was reached (52.4 %), as well as concentrations of N in aerial biomass (18.5 g kg-1) and aerial biomass yields (7.45 g pot-1) and radical (7.38 g pot-1), similar to those obtained with nitrogen fertilization. It is concluded that the co-inoculation with G. diazotrophicus and F. mosseae is effective in improving nitrogenous nutrition and biomass yields of Megathyrsus maximus cv. Likoni. Key words: rhizobacteria, arbuscular mycorrhizae, nitrogen, growth